Editor's Introduction: The Affective Modalities of Media and Technology. Issue 1 (1st June 2021) - Ball, Andrew J.
Abstract : The six essays in this in this issue of Screen Bodies explore what we might call the affective modalities of media, that is, each author examines the potential of emerging and traditional media to transform individual and collective relations through the strategic use of embodied affective experience. Three essays in the issue focus on new and emerging technology. In, "The iAnimal Film Series: Activating Empathy Through Virtual Reality, " Holly Cecil examines the potential power of virtual reality to generate empathy in users. In particular, she looks at the way animal advocacy organizations combine documentary film and virtual reality to communicate the embodied experience of living and dying in a factory farm to provoke feeling and widespread opposition to the industry.